Posterior communicating artery aneurysm presenting with haemorrhage into an arachnoid cyst. Issue 4 (1st April 1998) - Barker, R A; Phillips, R R; Moseley, I F; Taylor, W J; Kitchen, N D; Scadding, J W
Abstract : A patient is reported on with a subarachnoid haemorrhage (SAH) from an aneurysm of the posterior communicating artery, who initially presented with a sentinel bleed into an arachnoid cyst and normal magnetic resonance angiography (MRA) of the intracranial vasculature which led to a delay in diagnosis. Although this is a very rare presentation of a relatively common condition, it is important to recognise the importance of intracystic haemorrhage in such circumstances as well as the limitations of MRA, as a delay in diagnosis may have serious clinical consequences.